Cost benefit analysis of early thrombolytic treatment with intracoronary streptokinase. Twelve month follow up report of the randomised multicentre trial conducted by the Interuniversity Cardiology Institute of The Netherlands. Issue 5 (May 1988) - Vermeer, F; Simoons, M L; de Zwaan, C; van Es, G A; Verheugt, F W; van der Laarse, A; van Hoogenhuyze, D C; Azar, A J; van Dalen, F J; Lubsen, J
Abstract : The costs and benefits of early thrombolytic treatment with intracoronary streptokinase in acute myocardial infarction were compared in a randomised trial. All hospital admissions were recorded and the functional class was assessed at visits to the outpatient clinic during a 12 month follow up of 269 patients allocated to thrombolytic treatment and of 264 allocated to conventional treatment. Mean survival during the first year was calculated for patients with inferior and with anterior infarction and adjusted for impaired quality of life in cases where there were symptoms or hospital admission. In patients with inferior infarction mean survival was 337 days (out of a total follow up of 365 days) for patients allocated to thrombolytic treatment and 327 days for controls. Quality adjusted survival was seven days longer in the thrombolysis group (307 vs 300 days in controls). In patients with anterior infarction mean survival was significantly longer (35 days) in the thrombolysis group than in the control group as was quality adjusted survival (38 days) (304 vs 266 days in controls). The gain in life expectancy with thrombolytic treatment was 0.7 years for patients with inferior infarction, 2.4 years for patients with anterior infarction, and 3.6 years for the subset of patients with large anterior infarction who were admitted within two hours of the onset of symptoms.(ABSTRACT TRUNCATED AT 250 WORDS)